The Impact of Using Waiting Lines on Logistics Services at Port Sudan Port: A Theoretical Study - Abdelgadir, Somaia Osman Mohamed; Ahmed, Ahmed Osman Ibrahim (Journal of Ecohumanism, 2024)
The topic of waiting lines and its impact on logistics services at Port Sudan Port was addressed after the researchers noticed the size of the congestion of goods and the suffering of customers due to the delay in receiving their various shipments, as well as the long wait of ships until they are unloaded at Port Sudan South Port. The research aimed to provide an explanation of how waiting times affect the efficiency of logistics operations at the port. The research was based on the hypothesis of examining the expected effects of the average waiting time. The research relied on interviews, observation and surveys as a method of collecting information. The study reached a set of results, perhaps the most prominent of which is: The length of the waiting period was higher than its normal rates prevailing in various regional ports in neighboring countries, not to mention the global ones that are characterized by high operational efficiency. This indicates the importance of this study being followed by more studies that should be concerned with analyzing the reasons for this significant delay in handling compared to regional ports around Sudan. As previously mentioned, the study recommends conducting research and analytical studies in this regard by working on developing a quantitative model that helps port officials manage logistics services better, which will contribute to solving many problems related to logistics management as well as achieving more customer satisfaction, especially if we know that this port can be a window for a number of neighboring countries that suffer from the lack of an outlet to the sea, such as (South Sudan, Ethiopia and Chad).